Effects of Performance Appraisal System on Employees’ Performance in the Joint Venture Banks of Nepal - Kandel, Laxman Raj (Management Dynamics, 2021)
This study examines the effects of performance appraisal systems on employees’ performance in joint venture banks. It focuses on the employees’ awareness of the appraisal system and their knowledge of the appraisal system and performance appraisal management, leading to effective employee performance in joint venture banks. This was a research project that was meant to be descriptive. Questionnaires were the methods of data collection and 100 respondents from Everest bank, Himalayan bank and NABIL bank were studied. Moreover, the collected data were analyzed and processed using a computer program (excel) and indicated clearly on tables. The study results exposed that employee performance appraisal at Everest bank, Himalayan bank and NABIL bank is not effective and not very well utilized. The mainstream employees were unaware and were absent knowledge of the performance appraisal practiced in their organizations. They were not involved in an argument with supervisors and were not given sufficient time to organize for the meeting as an outcome; there’s no feedback delivered to employees afterwards appraisal. These banks do not use the available appraisal system for making important employee decisions. Employee performance appraisal should be implemented properly to meet a certain organization’s context, according to the recommendations, communication between employees and management decisions like disciplinary actions, promotion and training.